2016
DOI: 10.3390/s16111808
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Raman Spectroscopy Analysis of Polyhydroxyalkanoates Produced by Cupriavidus necator H16

Abstract: We report herein on the application of Raman spectroscopy to the rapid quantitative analysis of polyhydroxyalkanoates (PHAs), biodegradable polyesters accumulated by various bacteria. This theme was exemplified for quantitative detection of the most common member of PHAs, poly(3-hydroxybutyrate) (PHB) in Cupriavidus necator H16. We have identified the relevant spectral region (800–1800 cm−1) incorporating the Raman emission lines exploited for the calibration of PHB (PHB line at 1736 cm−1) and for the selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The methodology introduced here to rationally determine minimal sampling depth for a given population is generally applicable. It should not only guide the design of future studies, but also enable retrospective assessment of past studies that either sampled at only a few cells per population [ 24 26 ] or offered no rationale for their choice of sampling depth for a particular system [ 19 , 22 , 23 , 27 , 28 ]. Our study also suggests that efforts to automate SCRS acquisition from a given sample will be highly valuable, as it might allow routine analysis at sampling depth of dozens or even hundreds of cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology introduced here to rationally determine minimal sampling depth for a given population is generally applicable. It should not only guide the design of future studies, but also enable retrospective assessment of past studies that either sampled at only a few cells per population [ 24 26 ] or offered no rationale for their choice of sampling depth for a particular system [ 19 , 22 , 23 , 27 , 28 ]. Our study also suggests that efforts to automate SCRS acquisition from a given sample will be highly valuable, as it might allow routine analysis at sampling depth of dozens or even hundreds of cells.…”
Section: Resultsmentioning
confidence: 99%
“…This is important as many factors including the potential overlaps of Raman bands assignment among compounds, choice of sample pre-treatment methods, parameters of Raman measurement and species-specific property of microalgae can all potentially limit the practicability and reliability of SCRS in generating the measurements in a quantitative and ‘landscape-like’ manner. (iii) To derive the overall content and its degree of variation for target molecules in a cellular population, most studies have either sampled cells at a very low sampling depth [ 24 26 ], i.e., the number of cells measured for SCRS (e.g., only three cells sampled from each population [ 24 ]), or have not provided any rationale for their choice of sampling depth [ 19 , 22 , 23 , 27 , 28 ]. In fact, the link between method performance and sample depth, an experimental parameter directly determining throughput and common to all SCRS-based experiments, has not been critically probed.…”
Section: Introductionmentioning
confidence: 99%
“…We used a commercial Renishaw Raman microspectrometer (Renishaw inVia, Renishaw plc., Wotton-under-Edge, UK), with a 785 nm diode laser as the excitation source. The laser beam was focused on the sample with a microscope lens (Leica, Wetzlar, Germany, 50×, NA 0.5), the laser spot diameter was 2 µm × 10 µm (note that this laser spot shape is characteristic for the Renishaw InVia instrument [51,64,65]).…”
Section: Methodsmentioning
confidence: 99%
“…Raman spectra from living microorganisms contain multiple spectral peaks corresponding to unique interatomic vibrations in biomolecules, e.g., nucleic acids, proteins, carbohydrates, and lipids [51,52,53,54]. It has been shown that Raman microspectroscopy and Raman imaging can be regarded as the methods of choice for many studies of microorganisms, cells and other biological samples [51,55,56,57,58,59,60,61,62,63,64,65]. Detailed databases of Raman spectral features encountered in biological samples had been published before [60].…”
Section: Introductionmentioning
confidence: 99%
“…The use of internal standard (IS) in Raman is reported in the literature with good results for different analytes (A) and samples (S). Among the main uses are (IS/A/S): 4-mercaptopyridine/3,4-methylenedioxymethamphetamine and α-methyltryptamine hydrochloride/drugs [18]; d-nicotine/nicotine/liquids for electronic cigarettes [19], amide/poly(3-hydroxybutyrate)/bacteria [20]; OH stretching band of water/sulfate/aqueous solution [21]; 1-propanethiol/polycyclic aromatic hydrocarbons/food contact materials [22]. However, the selection of a suitable IS for a specific problem is still a challenge.…”
Section: Introductionmentioning
confidence: 99%